Secretion of protein from salivary glands in the ferret in response to vasoactive intestinal peptide. - Ekström, J (1989)
1. Secretory responses of ferret parotid and submandibular glands were investigated in the presence of muscarinic, alpha- and beta-adrenoceptor blocking agents. 2. In pentobarbitone-anaesthetized animals I.V. doses of vasoactive intestinal peptide (VIP) failed to elicit overt secretion of saliva from either gland. 3. However, an occult secretion of protein occurred in response to VIP from both types of gland. This was revealed by means of a subsequent I.V. wash-out injection of substance P, which is a potent secretagogue in ferrets. This effect of VIP was much more marked in the submandibular than in the parotid gland. 4. Electrical stimulation of the chorda-lingual nerve gave rise to protein secretion in the submandibular gland at subthreshold frequencies for overt non-cholinergic, non-adrenergic secretion of saliva, as revealed by subsequent wash-out I.V. injection of substance P. 5. Protein secretion in response to VIP was also demonstrated in vitro by perifusing small pieces of the two glands. The sensitivity of submandibular tissue to VIP greatly exceeded that of the parotid tissue. 6. It is concluded that VIP, or a structurally related peptide, may be involved in the non-cholinergic, non-adrenergic secretory response of ferret salivary glands evoked by parasympathetic nerve stimulation.